Control of myeloid cell functions by nociceptors - Hanč, Pavel; Messou, Marie-Angèle; Wang, Yidi; von Andrian, Ulrich H. (Frontiers in Immunology, 2023)
The immune system has evolved to protect the host from infectious agents, parasites, and tumor growth, and to ensure the maintenance of homeostasis. Similarly, the primary function of the somatosensory branch of the peripheral nervous system is to collect and interpret sensory information about the environment, allowing the organism to react to or avoid situations that could otherwise have deleterious effects. Consequently, a teleological argument can be made that it is of advantage for the two systems to cooperate and form an “integrated defense system” that benefits from the unique strengths of both subsystems. Indeed, nociceptors, sensory neurons that detect noxious stimuli and elicit the sensation of pain or itch, exhibit potent immunomodulatory capabilities. Depending on the context and the cellular identity of their communication partners, nociceptors can play both pro- or anti-inflammatory roles, promote tissue repair or aggravate inflammatory damage, improve resistance to pathogens or impair their clearance. In light of such variability, it is not surprising that the full extent of interactions between nociceptors and the immune system remains to be established. Nonetheless, the field of peripheral neuroimmunology is advancing at a rapid pace, and general rules that appear to govern the outcomes of such neuroimmune interactions are beginning to emerge. Thus, in this review, we summarize our current understanding of the interaction between nociceptors and, specifically, the myeloid cells of the innate immune system, while pointing out some of the outstanding questions and unresolved controversies in the field. We focus on such interactions within the densely innervated barrier tissues, which can serve as points of entry for infectious agents and, where known, highlight the molecular mechanisms underlying these interactions.